2009
DOI: 10.1016/s0924-9338(09)71491-9
|View full text |Cite
|
Sign up to set email alerts
|

Burnout or Professional Exhaustion Syndrome Among Primary Care Tunisian Doctors

Abstract: The Burnout or the professional exhaustion syndrome is common among doctors, especially primary care practitioners. The rates range from 25 to 76% according to specialties.Aims:Main objective was to assess the prevalence of burnout in Tunisian primary care practitioners working in public sector in the region of the Cap Bon. Secondary objectives were to determine the risk factors and the consequences associated with this syndrome.Methods:transversal study using four scales: Anonymous auto questionnaire elaborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Among hospital physicians the highest prevalence was found among the Internal Medicine physicians (69.64%). This study revealed a higher prevalence rate of burnout among study participants than what was found by others in the region; in Yemen it was (11.7%) [ 5 ] Whereas among Tunisia primary care doctors it was (33%) [ 6 ], and in Saudi Arabia the prevalence rate of burnout syndrome among female physicians working in the ministry of health hospitals in Jeddah city was (7.3 %) [ 7 ]. In other areas of the world several studies also showed that burnout is less prevalent than our study; Linzer et al (2001) and Bergner (2004), estimated that (22%) of physicians in the USA, (27%) of physicians in Great Britain [ 17 ], and (20%) of physicians in Germany suffer from burnout [ 18 ].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Among hospital physicians the highest prevalence was found among the Internal Medicine physicians (69.64%). This study revealed a higher prevalence rate of burnout among study participants than what was found by others in the region; in Yemen it was (11.7%) [ 5 ] Whereas among Tunisia primary care doctors it was (33%) [ 6 ], and in Saudi Arabia the prevalence rate of burnout syndrome among female physicians working in the ministry of health hospitals in Jeddah city was (7.3 %) [ 7 ]. In other areas of the world several studies also showed that burnout is less prevalent than our study; Linzer et al (2001) and Bergner (2004), estimated that (22%) of physicians in the USA, (27%) of physicians in Great Britain [ 17 ], and (20%) of physicians in Germany suffer from burnout [ 18 ].…”
Section: Discussionmentioning
confidence: 65%
“…It is remarkably stable when studied across time on the same individuals and this chronic nature of burnout is probably not due to its genetic or personality origins but rather to work-related characteristics [ 4 ]. Several studies were conducted to study burnout in the Eastern Mediterranean region; In Yemen it was (11.7%) [ 5 ], While among Tunisian primary care doctors there was (33%) suffering from burnout (35%) of them had high score of emotional exhaustion, (21%) had high depersonalization and (40%) had a low score of personal accomplishment [ 6 ], and in Saudi Arabia,Selaihem found Prevalence of burnout amongst physicians working in primary care in Riyadh military hospital, Saudi Arabia (2013) was (53.5%) of respondents scored high for EE burnout, (38.9%) for DP and (28.5%) for PA, with (2.78%) scoring high burnout in all three dimensions [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…5 In Tunis, professional burnout was significantly associated with depression, suicidality, and anxious temperament whereas professional exhaustion greatly impacted the relationships with patients and colleagues. 6 In Jordan, a study observed the highest prevalence of stress among GPs and dentists, followed by pharmacists and specialist physicians. Stress was more pronounced in women.…”
Section: Journal Of the Bahrain Medical Societymentioning
confidence: 99%